Plan estratégico de marketing para la distribuidora Samaniego de la ciudad de Loja, periodo 2013-2018. - Ramírez Feijoo, Lesly Verónica (2014)
This thesis project involves the development of a STRATEGIC MARKETING PLAN FOR THE DISTRIBUTOR SAMANIEGO CITY Loja, PERIOD 2013-2018 that would promote the development and growth of the company the subject of this study, which was conducted in based on theoretical underpinnings and field information obtained through the use of surveys of 126 customers, 10 employees and an interview with the manager. The process of investigating this issue, some from making a situational analysis of the company. Upon surveys to customers and employees, the manager interview and direct observation, has given us an overview of current business conditions and their social environment. This first external analysis was performed in the business, which enabled us to define the opportunities and threats thereof, whereby the EFE matrix, wherein the weighted total is 2.65 was constructed, indicating that the weight of the opportunities is greater than the impact of threats. Then using the internal analysis of the firm a diagnosis of which was conducted, whereby the strengths and weaknesses are determined, and thus the EFI matrix gave the weighted score 2.40 was developed, which means that the company is weak internally. With internal and external analysis SWOT matrix that allowed us to identify opportunities, threats, strengths and weaknesses, so that the matrix of high impact with what we proceeded to do the merge FO, DO, FA was built was built, DA resulting in the strategic objectives. With the definition of the strategic objectives developed a STRATEGIC MARKETING PLAN FOR THE DISTRIBUTOR SAMANIEGO CITY Loja, PERIOD 2013-2018, which will help the organization capture new customers, increase sales and generate superior returns for its partners. Finally we define the main conclusions that we arrived after finishing the research work.